Old People as Victims of Crimes Against Live and Health - Gęsicki, Marcin; Trnka, Jakub; Susło, Robert; Siuta, Jędrzej; Drobnik, Jarosław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Based on ZMS in Wroclaw analyzed data on crimes against life and health of older people carried out. They represent approximately 6% of offenses of this type. Frequently the perpetrator was known to the victim, although he was not a family member. Followed in frequency involved family members. More often, the perpetrator was a man than a woman. The perpetrator is most often used a blunt tool. The mechanism of injury in those patients was usually followed by a fall from hitting the ground. A common mechanism were also pushing and pulling. Patients studied there were of serious injuries such as vertebral fracture mechanism such as fall to the ground. Damage occurred in the elderly are more serious than if similar measures were younger.